Frege on Absolute and Relative Truth - Pardey, U. author. aut Link
XXIV, 242 p.
Keywords: This book has two objectives: to be a contribution to the understanding of Frege's theory of truth – especially a defence of his notorious critique of the correspondence theory - and to be an introduction to the practice of interpreting philosophical texts.